Chiral nanoprobes for targeting and long-term imaging of the Golgi apparatus. Issue 10 (14th August 2017) - Li, Rong Sheng; Gao, Peng Fei; Zhang, Hong Zhi; Zheng, Lin Ling; Li, Chun Mei; Wang, Jian; Li, Yuan Fang; Liu, Feng; Li, Na; Huang, Cheng Zhi
Abstract : The targeting and long-term imaging of the Golgi apparatus have been realized via l -cysteine functionalized nanoprobes. Abstract : The Golgi apparatus is an essential subcellular organelle. Targeting and monitoring the Golgi change at the single-cell level over a long time scale are critical but are challenges that have not yet been tackled. Inspired by the precise Golgi positioning ability of galactosyltransferase and protein kinase D, due to their cysteine residues, we developed a method for long-term Golgi imaging. Fluorescent molecules, carbon quantum dots (CQDs) and silica nanoparticles could target the Golgi when they are modified withl -cysteine.l -Cysteine-rich chiral carbon quantum dots (LC-CQDs), which have the benefits of a high Golgi specificity froml -cysteine and excellent photostability and biocompatibility from the CQDs, are proven to be highly suitable for long-term in situ imaging of the Golgi. Investigation of the mechanism showed that free thiol groups and thel -type stereo configuration of LC-CQDs are essential for specific targeting of the Golgi. With the aid of the as-prepared LC-CQDs, the dynamic changes of the Golgi in the early stage of viral infection were visualized. The Golgi targeting and imaging strategy used in this work is beneficial for Golgi-targeted drug delivery and early diagnosis and therapy of Golgi diseases.